Enhanced Anaerobic Digestion of Food Waste by Supplementing Trace Elements: Role of Selenium (VI) and Iron (II) - Ariunbaatar, Javkhlan; Esposito, Giovanni; Yeh, Daniel H.; Lens, Piet N. L. (Frontiers in Environmental Science, 2016)
This paper discusses the potential to enhance the anaerobic digestion of food waste FW by supplementing trace elements (Fe, Co, Ni, Zn, Mn, Cu, Se, and Mo) individually as well as in cocktails. A series of batch experiments on the biomethane potential of synthetic food waste were performed with low (FW-A) and high (FW-B) trace element background concentrations prepared in, respectively, Delft (The Netherlands) and Tampa (Florida, USA). The most effective trace elements for FW-A were Fe with an increase of 39.2 (± 0.6) % of biomethane production, followed by Se (34.1 ± 5.6 % increase), Ni (26.4 ± 0.2 % increase) and Co (23.8 ± 0.2 % increase). For FW-B supplementing these trace elements did not result in enhancement of the biomethane production, except for Se. FW-B had a Se concentration of 1.3 (± 0. 5) µg/gTS, while it was below the detection limit for FW-A. Regardless of the FW source, Se resulted in 30 – 35% increase of biomethane production at a concentration range of 25-50 µg/L (0.32 – 0.63 µM). Volatile fatty acids analysis revealed that TE supplementation enhances their consumption, thus yielding a higher biomethane production. Moreover, additional experiments on sulfide inhibition showed the enhancing effects of trace elements on the anaerobic digestion of food waste were not related with sulfide toxicity, but with the enzymatic reactions and/or microbial biomass aggregation.